Advancing Competitiveness and Developing the Innovation and Investment Potential of Industrial Enterprises Using Cluster Strategies - MADIYAROVA, Diana; ŁUNIEWSKI, Artur; IBRAEVA, Aliya (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019DO - 10.14505/jarle.v10.8(46).20, 2019)
This study investigates the mechanism of formation of competitive advantages and competitive factors influencing the competitiveness of industrial production. Analyzing the views of foreign and local researchers on the formation of competitive advantages of industrial enterprises, we consider the diversification of industrial enterprises for intra-cluster optimization as well as the ways to improve the economic efficiency of optimization of industrial enterprises. The trends to increase economic efficiency of optimization of industrial sphere enterprise performance are presented. It can be concluded that its evaluation is a procedure that allows presenting objective results of the activities of the evaluated enterprises, both current and prospective, obtained in the framework of the implementation of the overall development strategy by influencing various groups of efficiency factors.